PENGARUH STRATEGI PEMBELAJARAN DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SEJARAH KEBUDAYAAN ISLAM SISWA MADRASAH ALIYAH NEGERI SIMALUNGUN - Nurhayatimah Sinaga (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to find out and to describe: (1) the learning outcomes ofSKI students taught using CIRC learning strategies are higher than thelearning outcomes of students taught using expository learning strategies,(2) SKI learning outcomes between students with high learningindependence than results student learning with low learningindependence, and (3) the interaction between learning strategies andlearning independence towards learning outcomes of SKI. The populationof this research is all students of class X MAN Simalungun consists of 5classes. Based on Cluster Random sampling technique. The researchinstrument is a test used to obtain learning outcome data andquestionnaires to obtain data on student learning independence. Theanalysis technique is two-way Anova at significance  = 0.05 followed bythe Scheffe test. The results showed: (1) the average SKI learning outcomesof students taught with CIRC learning strategies ( X = 29.32) were higherthan the average SKI learning outcomes of students taught withexpository learning strategies ( X = 27) with Fcount = 13,32 > Ftable = 4.00, (2)the average SKI learning outcomes of students with high learningindependence ( X = 29.90) are higher than students' SKI learning outcomeswith low learning independence ( X = 26.20), with Fcount = 10.41 > Ftable =4.00, and (3) there is an interaction between learning and independencelearning strategies with Fcount = 12.51 > Ftable = 4.00.